Design and Performance Analysis of Strip Photonic Waveguide with Coating Layer for Multimode Propagation - Chandra, Veer (Micro and Nanosystems, 2024)
Introduction: Photonic devices play a pivotal role in the realm of high-speed data communication due to their inherent capability to expedite the transfer of information. Historically, research efforts in this domain have predominantly concentrated on investigating the fundamental mode propagation within photonic waveguides. Methods: This study diverges from the conventional approach by delving into the untapped potential of higher-order modes in addition to the fundamental mode of propagation. The exploration of these higher-order modes opens up new possibilities for optimizing and enhancing the performance of photonic devices in high-speed data communication scenarios. As a distinctive aspect of this study, various coating materials were scrutinized for their impact on both fundamental and higher-order mode propagation. The materials under examination included AlN (aluminum nitride), Germanium, and Silicon. These materials were chosen based on their unique optical properties and suitability for influencing different modes of light propagation. The findings from the study reveal that applying a coating of germanium demonstrates advantageous characteristics, particularly in terms of reduced signal loss, even when considering higher-order modes of propagation within photonic devices. Results: In this context, the results indicate that germanium-coated waveguides exhibit notably low propagation losses, with measurements as minimal as 0.25 dB/cm. This low level of loss is particularly noteworthy, especially when the waveguide has a width of 550 nm and is coated with a thickness of 50 nm. The dimensions and coating specifications play a crucial role in determining the efficiency of light transmission within the waveguide. Conclusion: The fact that the propagation loss is substantially low under these conditions suggests that the germanium-coated waveguide, even when considering higher-order modes of light propagation, can effectively maintain the integrity of the optical signal.
Keywords: multimode